2011
DOI: 10.3892/ijmm.2011.704
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glypican-3 expression via RNA interference influences the growth and invasive ability of the MHCC97-H human hepatocellular carcinoma cell line

Abstract: Abstract. Glypican-3 (GPC3), a membrane-bound heparan sulfate proteoglycan, is found to be overexpressed in hepatocellular carcinoma (HCC). The purpose of the present study was to investigate the possible role of GPC3 in the development of HCC. In this study, RNA interference (RNAi) with a GPC3 small hairpin RNA (GPC3 shRNA) was used to identify the effects of GPC3 on the regulation of malignant behaviors of HCC. MHCC97-H, a highly metastatic human HCC cell line in which GPC3 mRNA and protein levels were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…A previous study demonstrated that inhibition of the GPC3 expression of HCC cells through RNA interference reduced the tumorigenicity in nude mice, which indicated that GPC3 may be a potential molecular target in HCC therapy ( 28 ). In further in vivo experiments, the present study identified that tumor nodule formation in nude mice, induced by HepG2 cells, was suppressed significantly following treatment with DCs-GPC3-CIKs, indicating that specific CIKs induced by DCs-GPC3 targeting of GPC3-expressing HCC cells exhibited strong antitumor activity against HepG2 xenografts in mice.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that inhibition of the GPC3 expression of HCC cells through RNA interference reduced the tumorigenicity in nude mice, which indicated that GPC3 may be a potential molecular target in HCC therapy ( 28 ). In further in vivo experiments, the present study identified that tumor nodule formation in nude mice, induced by HepG2 cells, was suppressed significantly following treatment with DCs-GPC3-CIKs, indicating that specific CIKs induced by DCs-GPC3 targeting of GPC3-expressing HCC cells exhibited strong antitumor activity against HepG2 xenografts in mice.…”
Section: Discussionmentioning
confidence: 99%
“…GPC3 modulates the effect of growth factors such as IGF-2, BMP-7 and FGF-2 on hepatoma cells [11,12] and may recruit M2 tumor-promoting macrophages to the HCC microenvironment [13]. Emerging evidence also suggests that inhibition of glypican-3 function via knockdown [14,15] or competition [12,16] has a profound negative effect on HCC proliferation. Expression on the cell surface makes GPC3 an attractive target for antibody-directed therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Glypican-3 appears critical for the association of growth factors such as insulin-like growth factor-2, bone morphogenic protein-7 and fibroblast growth factor-2 with growth factor receptors [11,12] but also may play an immunomodulatory role [13]. Inhibition of glypican-3 function via knockdown [14,15] or competition [12,16] has a profound negative effect on HCC cell line proliferation. Unlike any other tumor antigen associated with hepatocellular carcinoma, GPC3 is a glycophosphatidylinositiol-linked membrane-associated protein with a large extracellular domain attractive for antibody-directed therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Fresh culture medium was replaced every 3 d. After 21 d, the clones were fixed with methanol and stained with 2% Giemsa solution (Merck, New York, USA). The colonies were visualized and counted under a microscope, as previously described [ 35 ]. All experiments were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%